NICHE MARKET IN FANGIRLING PHENOMENON - Swandewi, Ni Kadek; Citrawati, Luh Putu; Asmarani, I.G.A. Ratih (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
Specific segmentation in managing the target audience in events can take advantage of phenomena or trends that are currently happening in society. One of the current familiar phenomena to millennials and gen Z is the phenomenon of "fangirling." Fangirl is a nickname for a group of girls who are highly dedicated to their idols and even become obsessed with them. This paper contains how the impact of using the fangirling phenomenon in marketing of a music event. The purpose of this article is to provide an overview of the implementation of the niche marketing strategy by the fangirls community carried out by ARMY Kuta Bali. By using qualitative research methods which describe the actual situation that occurred during the research and combined with theoretical references from both journals and articles related to business strategies. The findings of this study shows that fangirls who join a fandom have great potential to buy tickets to events held specifically for their favorite idols, being repeaters and also promoting event to other fangirls.